Strategi Komunikasi Politik Dalam Pemilihan Umum Di Era Digital - Majid, Nurcholis; Nur Hidayah, Aisyah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
Political communication has undergone fundamental changes due to the rapid expansion of digital media in general elections. Social media platforms, data-driven targeting, and interactive content have reshaped how political actors engage with voters. This study aims to systematically examine political communication strategies in digital-era elections by synthesizing empirical findings from international and Indonesian contexts. The research employs a qualitative literature-based approach, using a systematic review of peer-reviewed journal articles, conference proceedings, and scholarly book chapters published between 2014 and 2024. Data were analyzed through thematic content analysis to identify dominant strategic patterns, communication models, and their implications for democratic engagement. The findings show that digital political communication strategies increasingly emphasize disintermediation, microtargeting, platform diversification, and personalization of political messages. However, these strategies also generate challenges related to misinformation, uneven participation, and regulatory gaps. The study concludes that digital political communication enhances voter engagement and campaign efficiency but requires stronger ethical standards and institutional oversight to sustain democratic quality. This research contributes theoretically by integrating classical political communication theory with contemporary digital practices and practically by offering insights for electoral stakeholders in developing effective and accountable communication strategies.